answersLogoWhite

0

26= 2 x 2 x 2 x 2 x 2 x 2 = 64

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
JudyJudy
Simplicity is my specialty.
Chat with Judy
TaigaTaiga
Every great hero faces trials, and you—yes, YOU—are no exception!
Chat with Taiga
More answers

(-2)6 = (-2)*(-2)*(-2)*(-2)*(-2)*(-2) = 4*(-2)*(-2)*(-2)*(-2) = -8*(-2)*(-2)*(-2) = 16*(-2)*(-2) = -32*(-2) = 64

Alternatively, (-2)6 = [(-2)2]3 = 43 and you don't need to worry about the minus sign any more. And 43 = 64.

User Avatar

Wiki User

15y ago
User Avatar

2 to the 6th power is 64 :>

User Avatar

64

User Avatar

Anonymous

4y ago
User Avatar

12

User Avatar

Anonymous

4y ago
User Avatar

72

User Avatar

Anonymous

4y ago
User Avatar

2x2x2x2x

User Avatar

Anonymous

4y ago
User Avatar

7

User Avatar

Anonymous

4y ago
User Avatar

Add your answer:

Earn +20 pts
Q: What is -2 to the 6th power?
Write your answer...
Submit
Still have questions?
magnify glass
imp